Protocol for a nationwide case-control study of firearm violence prevention tactics and policies in K-12 schools - Buttar, Navjot; Rajan, Sonali; Klarevas, Louis; Prins, Seth J.; Heinze, Justin; Cheung, Ken; Rudolph, Kara E.; Goyal, Monika; Zeoli, April; Branas, Charles C. (PLOS ONE, 2024)
Background Most U.S. K-12 schools have adopted safety tactics and policies like arming teachers and installing metal detectors, to address intentional school gun violence. However, there is minimal research on their effectiveness. Furthermore, sociodemographic factors may influence their implementation. Controlled studies are necessary to investigate their impact on gun violence and related disciplinary outcomes. Objective The paper outlines the protocol for a case-control study examining gun violence prevention policies in U.S. K-12 schools. The study aims to investigate if there is an association between the total number and type of specific safety tactics and policies and the occurrence of intentional shootings in K-12 public schools, student disciplinary outcomes, and if urbanicity, economic, and racial factors modify these associations. Methods We will create a nationally representative dataset for this study and ascertain a full census of case schools (schools that experienced intentional gunfire on the campus during school hours since 2015) through national school shooting databases. Matched control schools will be randomly selected from U.S. Department of Education’s national database of all public schools. We will analyze 27 school safety strategies organized into seven key exposure groupings. Results Supported by the National Institutes for Child Health and Development (R01HD108027-01) and having received Institutional Review Board approval, our study is currently in the data collection phase. Our analytical plan will determine the association between the number and type of school safety tactics and policies with the occurrence of intentional shootings and suspensions and expulsions in a national sample of approximately 650 K-12 public schools. Additional analyses will investigate the effect modification of specific covariates. Conclusion As the first national, controlled study, its results will provide novel and needed data on the effectiveness of school safety tactics and policies in preventing intentional shootings at K-12 public schools.